Development and evaluation of a survey instrument to assess veterinary medical record suitability for multi-center research studies - Praczko, Dora; Tinkle, Amanda K.; Arkenberg, Crystal R.; McClelland, Robyn L.; Creevy, Kate E.; Tolbert, M. Katherine; Barnett, Brian G.; Chou, Lucy; Evans, Jeremy; McNulty, Kellyn E.; , Dog Aging Project Consortium; Levine, Jonathan M. (Frontiers in Veterinary Science, 2022)
Here we describe the development and evaluation of a survey instrument to assess the research suitability of veterinary electronic medical records (EMRs) through the conduct of two studies as part of the Dog Aging Project (DAP). In study 1, four reviewers used the instrument to score a total of 218 records in an overlapping matrix of pairs to assess inter-rater agreement with respect to appropriate format (qualification), identification match (verification), and record quality. Based upon the moderate inter-rater agreement with respect to verification and the relatively large number of records that were incorrectly rejected the instrument was modified and more specific instructions were provided. In study 2, a modified instrument was again completed by four reviewers to score 100 different EMRs. The survey scores were compared to a gold standard of board-certified specialist review to determine receiver operating curve statistics. The refined survey had substantial interrater agreement across most qualification and verification questions. The cut-off value identified had a sensitivity of 95 and 96% (by reviewer 1 and reviewer 2, respectively) and a specificity of 82% and 91% (by reviewer 1 and reviewer 2, respectively) to predict gold standard acceptance or rejection of the record. Using just qualification and verification questions within the instrument (as opposed to full scoring) minimally impacted sensitivity and specificity and resulted in substantial time savings in the review process.